Outlook of SNCA (?-synuclein) transgenic fly models in delineating the sequel of mitochondrial dysfunction in Parkinson's disease. - Samson, J.S.; Rajagopal, K.; Parvathi, V.D. (Brain Research, 2025)
Parkinson's disease (PD) is a progressive neurodegenerative disorder associated with mechanisms that results in loss of dopaminergic neurons in the substantia nigra pars compacta (SNpc) region of the brain. Being a complex heterogeneous disorder, there is a requisite in discovering the underlying molecular signatures that could potentially help in resolving challenges associated with diagnosis as well as therapeutic management. SNCA gene that encodes for the protein ?-synuclein is widely known for its indispensable role in aggravating the progression of sporadic and familial PD, upon mutations. Likewise, mitochondrial dysfunction is inferred to be playing a central role in both forms of PD. Observations from experimental models and human PD cases displayed strong evidence for disruption of mitochondrial dynamics, inhibition of mitochondrial complex I protein's function and elevation in reactive oxygen species (ROS) by the toxic aggregation of ?-synuclein. Further, recent studies have raised the possibility of an underlying relationship, where the ?-synuclein toxicity is exacerbated by the mutant mitochondrial complex proteins and vice-versa. In this review, we provide an overview of mechanisms influencing ?-synuclein-related neurodegeneration, particularly, emphasizing the role of SNCA (?-synuclein) gene in leading to altered mitochondrial biogenesis during PD. We have described how transgenic Drosophila models were reliable at recapitulating some of the essential characteristics of PD. In addition, we highlight the capability of utilizing transgenic fly models in deciphering the altered ?-synuclein toxicity and mitochondrial dysfunction, as induced by defects in the mitochondrial DNA.